2015
DOI: 10.1186/s12978-015-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unmet need for family planning among currently married women in Dangila town administration, Awi Zone, Amhara regional state; a cross sectional study

Abstract: BackgroundUnmet need for family planning is a major problem of developing countries. Evidences about unmet need for family planning and associated factors are not enough in Dangila town. Therefore, this study was done to assess the magnitude and determinants of unmet need for family planning among currently married women in Dangila town.MethodologyCommunity based cross sectional study design was used to collect data from a total of 551 currently married women from February to March 2014. Data were collected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
77
8
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 6 publications
27
77
8
5
Order By: Relevance
“…In this study, 707 (92.42%) of respondents ever used either of the modern FP methods. This finding is consistent with several studies [18][19][20].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, 707 (92.42%) of respondents ever used either of the modern FP methods. This finding is consistent with several studies [18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…The finding of this study coincide with study conducted in Mekele city and Assosa district among married women; majority of them ever used and have been using injectables and pills [19][20][21] and this was too much higher than a population based study in Mojo town which reported that from 551 respondents nearly 34% of them have ever practiced one form of FP methods during their life [16] and the study from South Central Ethiopia in which Current contraceptive prevalence rate was 25.4% (95% CI: 24.2, 26.5) [17] and this difference mainly might be attributed to expansion of health facility, increased Information, Education and communication (IEC) on FP methods which creates awareness and increased service seeking behavior in this study. Unlike the above disparities; the finding of this study yields closer result to a study conducted in the Dangila and Assosa zone [18,19]. In our study, majority 452 (71.5%) of them used FP to space the birth interval and 198 (31.3%) of them mentioned that to prevent unwanted pregnancy.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Although advances in family planning have been achieved globally, the unmet needs for planning continue to increase and become a serious problem in developing countries [1].…”
mentioning
confidence: 99%
“…[6] Various studies have explored the reasons of unmet need of FP across the globe as in-depth understanding of these reasons is necessary for addressing the gap of unmet need at programmatic level. Genet et al, in his study at Dangila, Amhara regional state, found 33% of women had lack of knowledge regarding risk of pregnancy by not practising FP methods, 32% reported fear of side effects, and 11.8% [15] cited religious prohibition as the principal reason for not availing FP services. Patel et al in his study reported lack of knowledge regarding contraceptive measures (55%) [16] and Raveendran and Vijayakuma from South India cited want of a male child in the future by spouse (63.3%) as the most important reason for unmet need.…”
Section: Discussionmentioning
confidence: 99%